2010
DOI: 10.1366/000370210791666255
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Raman Investigation of the Orientation of Collagen Fibrils and Crystallites in the Haversian System of Bone

Abstract: Knowledge of the organization of the components of bone is of primary importance in understanding how this tissue responds to stresses and provides a starting point for the design and development of biomaterials. Bone structure has been the subject of numerous studies. The mineralized fiber arrangement in cortical bone is either a twisted or orthogonal plywood structure. Both mineral models coexist in compact bone. Raman polarized spectroscopy offers definite advantages in the study of biological samples, enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…Notable differences in RS intensity between orthogonal bone orientations [ Fig. 3(e)] occur mostly at locations previously reported by the Penel group 8,26 to be sensitive to polarization: ν3 phosphate (1045 cm −1 ), amide III δðNHÞ band (1273 cm −1 ), 44 and amide I (1668 cm −1 ). The most striking differences occur at peak shoulders and would, therefore, be overlooked by many standard analyses.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Notable differences in RS intensity between orthogonal bone orientations [ Fig. 3(e)] occur mostly at locations previously reported by the Penel group 8,26 to be sensitive to polarization: ν3 phosphate (1045 cm −1 ), amide III δðNHÞ band (1273 cm −1 ), 44 and amide I (1668 cm −1 ). The most striking differences occur at peak shoulders and would, therefore, be overlooked by many standard analyses.…”
Section: Discussionmentioning
confidence: 70%
“…However, traditional peak ratios only report a small portion of the known spectral changes that occur with polarization as previously characterized by others. 8,18,[25][26][27] Moreover, limiting analysis to established peak ratios may overlook crucial aspects of complex toughness phenotypes if they manifest as subtle peak widening or shifting.…”
Section: Introductionmentioning
confidence: 99%
“…(15) Although their long axes align with that of the adjacent collagen fibril, the planes of stacks around and between fibrils may not be similar; there is some evidence that they vary significantly across local areas. (54) In addition to the highly ordered mineral platelet arrays/stacks, there is a disorganized hydrogen-phosphate phase, with both the ordered and disordered mineral elements being strongly associated with both citrate and water. (1) A recent article suggests that citrate acts to maintain the ordered platelet parallel arrays and also holds nonplatelet hydrogen-phosphate in a relatively immobile, highly hydrated phase between the platelets, thus maintaining a degree of disorder and preventing crystals increasing in size or thickness (which would result in increased bone fragility).…”
Section: Mineral Plateletsmentioning
confidence: 99%
“…We chose the v 2 PO 4 and the amide III bands as it was previously shown that they have minimal susceptibility to tissue organization/orientation effects. [18][19][20][21][22] The Ca content (Ca mass fraction) was derived from BE signal intensities (gray levels in qBEI image) that reflect the local electron density of the bone material. For this purpose, the gray levels were standardized against reference materials (carbon and aluminum) with known electron densities (atomic numbers).…”
Section: Introductionmentioning
confidence: 99%